Metal-free synthetic organic dyes - Ziarani, Ghodsi Mohammadi; Moradi, Razieh; Lashgari, Negar; Kruger, Henk G. (Elsevier, 2018)
Metal- Free Synthetic Organic Dyes is a comprehensive guide to the synthetic, organic dyes that are classified by their chemical structure. As synthetic dyes are playing an increasingly important role in modern life, with applications in both industry and scientific research, this book provides insights on the many research attempts that have been made to explore new photosensitizers in the development of dye sensitized solar cells (DSCs). These novel photosensitizers have incorporated, within their structure, different organic groups, such as coumarins, cyanines, hemicyanines, indolines, triphenylamines, bis(dimethylfluorenyl) aminophenyls, phenothiazines, tetrahydroquinolines, carbazoles, polyenes, fluorenes, and many others. This comprehensive resource contains color figures and schemes for each dye discussed, and is an invaluable resource for organic, inorganic and analytical chemists working in academia and industry.